PEMBERIAN TRICHOKOMPOS BEBERAPA BAHAN ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS ( Zea mays saccharata sturt ) . - Rugun Hartati; Husna Yetti; Fifi Puspita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study attempts to identify the effects the provision of various trichokompos from organic matter and get trichokompos the best on the growth of and crop production sweet corn ( Zea mays saccharata sturt.). Study using random design complete ( RAL ) consisting of 4 treatment, each’s treatment repeated five times in order to obtain 20 units of experiments, the treatment is provided: K0 = without trichokompos, T1 = 15 ton / ha trichokompos rice straw, T2 = 15 ton/ha trichokompos TKKS, T3 = 15 ton/ha trichokompos dregs know and T4 = trichokompos rice straw + TKKS + dregs know . Parameter examined is tall plant, broad leaves, appear male flowers, appear the female flowers, age harvest, heavy tongkol berkelobot, Long cobs, the diameter of the tunny, heavy tongkol without kelobot and heavy tongkol per bedengan. Implication that can be drawn from the result of this research is to get growth and the production of of a corn plant sweet better suggested treat trichokompos a mixture of the trichokompos rice straw + TKKS + dregs know . Keywords : Sweet corn, Trichokompos